BENTUK KALIMAT INFORMAL PADA INTERAKSI SISWA KELAS 8 DENGAN GURU SMPN 10 MALANG DALAM PEMBELAJARAN BAHASA INDONESIA - Nisrina Azkia Nazhifa; Vanda Hardinata (Jurnal Bastra (Bahasa dan Sastra), 2025)
This article aims to explain the form of informal sentences in the interaction of students with students and students with teachers who use code mixing and the influence of informal sentences in improving the process of learning success. This study employs a qualitative research design with a descriptive method supplemented by observation techniques. The data source is 8th grade students and Indonesian language teachers from SMPN 10 Malang, and the data are informal utterances used in interaction with one another. The presented data will be used to draw conclusions from the previously presented data. The results show that there are 5 data on the form of informal sentences used in student interactions with students and 5 data on the form of informal sentences used in student interactions with teachers. Increasing the success process of learning Indonesian can be influenced by the use of informal sentences. In the field of education, namely in the scope of learning, this can reduce the use of Indonesian sentences that follow the linguistic rules that should use formal Indonesian sentences.